2023
DOI: 10.1001/jamapediatrics.2023.0763
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and Return on Investment of a Nationwide Case-Finding Program for Familial Hypercholesterolemia in Children in the Netherlands

Abstract: ImportanceThe Netherlands is one of the few countries that has a long-term history of active screening for familial hypercholesterolemia (FH), enabling health-economic analyses.ObjectiveTo investigate cost-effectiveness and the return on investment (ROI) of a nationwide cascade case-finding and preventive treatment program starting with identification of FH in children and treatment, from both a societal and health care perspective.Design, Setting, and ParticipantsCascade case-finding and early preventive trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
(101 reference statements)
0
23
0
Order By: Relevance
“…44 Similar studies were conducted in Australia and the Netherlands. Ademi et al 38,45 the economic aspects of cascade screening for 10-year-old children from the perspectives of the Australian public healthcare system and Dutch healthcare and society, respectively. Results consistently showed that cascade screening for 10-year-old children was cost-effective compared to standard care in both Australia and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Similar studies were conducted in Australia and the Netherlands. Ademi et al 38,45 the economic aspects of cascade screening for 10-year-old children from the perspectives of the Australian public healthcare system and Dutch healthcare and society, respectively. Results consistently showed that cascade screening for 10-year-old children was cost-effective compared to standard care in both Australia and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis excluded literature that did not provide specific cost or outcome values 33,39,44 and literature where strategies were not comparable. 31,32,35,42,43,46 The final synthesis of results included eight studies on cascade screening 30,34,37,38,40,41,45,47 and three studies on Universal Screening. 25,34,36 These studies considered outcome measures such as QALY, LYG, adverse events averted, and deaths averted, resulting in the eventual synthesis of seven distinct groups (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic evaluations can guide uptake at scale, particularly if they include implementation costs and long-term outcomes. There are some economic data on the use of genetic testing to identify FH in US adults, in children outside the US, and on cascade FH screening in adults, and there is 1 recent cost analysis of childhood universal vs targeted lipid screening for hyperlipidemia; however, there are no cost-effectiveness analyses of lipid-based screening for FH in children assessing downstream health outcomes. Cost-effectiveness of childhood lipid screening is likely to vary by disease targeted (primary vs secondary lipid disorders), disease prevalence in the population, and the cost of testing and follow-up.…”
mentioning
confidence: 99%
“…However, observational and genetic data show that lowering LDL-C concentrations reduces progression of subclinical ASCVD and prevents clinical events . Cholesterol screening is critical for early diagnosis of FH and, with clinical assessment and genetic testing, cost-effectively enables cascade testing of close relatives . The International Atherosclerosis Society recently published clinical and implementation guidance on the care of FH, advocating for use of integrated screening and testing methods for FH in adult and pediatric individuals .…”
mentioning
confidence: 99%